Doctoral canons in Portugal: social origins and careers of an ecclesiastical elite (16th and 17th centuries) - López-Salazar, Ana Isabel (Cuadernos de Historia Moderna, 2021)
The aim of this paper is the study of the geographical origins, the careers in University, Church and Administration, and the social background of the Portuguese doctoral canons in 16th and 17th centuries. It was a very specific group within the Portuguese Church, since the King was the royal patron of the doctoral canonries, and these benefices were granted after a public examination at the University of Coimbra. The analysis of the social origins of these canons shows that the doctoral canonries were mostly in the hands of untitled aristocracy (fidalguia), local elites –both in cities and rural areas–, and groups linked to the royal service in the Administration.